Evaluating of the Fifth Graders’ Performance in Reciting the Holy Quran in Mafraq in light of the Standard Criteria - Al Zubi, Ibrahim (Jordan Journal of Educational Sciences, 2013)
The present study aimed to identify the evaluation of the fifth graders performance level in reciting the Holy Quran in Mafraq in light of the standard criteria. The study sample consisted of 63 students who were selected intentionality from the Directorate of Education in Mafraq, Jordan. A questionnaire was designed to evaluate the students reciting in light of the three standards of recitation, including different rules of reciting m and n sounds. The results of the study showed that the level of performance of fifth basic graders is low in general. It is recommended that an educational program is built to improve the Koran recitation in light of the standard levels to improve their indicators, and the specific rules, and further studies be conducted in this field